THE EFFECT OF DISCIPLINE, ORGANIZATIONAL COMMITMENT AND WORK ENVIRONMENT TO GAIN TEACHER PERFORMANCE IN PAUD - Sulistiadi, Andi; Sihite, Otto Berman; Alamsyah, Virza Utama (Department of Management, 2019)
This writing aims to prove several HR variables that affect the performance of teachers in this digital learning era. In this era of digital learning, it is believed that the role of the teacher as a channel for children's educators is even replaced by the digital device. Based on this phenomenon, teacher performance is assumed to decrease. This research was conducted at Pelita Harapan BangsaTegal. The study population was 57 teachers and data collection techniques were carried out by distributing questionnaires and the data were analyzed using the Smart PLS research tool.3.0. The results of the analysis show that the HR variable consisting of Work discipline, Organizational Commitment and the Work Environment positively influences teacher performance. HR strategies have positive effects such as: disciplining all levels, expressed organizational commitment and fulfillment, and work costs that are designed as comfortable as possible for teachers can improve.